Community and Intellectual Happiness: The Invention of a Shifting Logical Subject - Ardizzone, Maria Luisa (Reading as the Angels Read, 2016)
In evaluating the comment (III.3.13) to lines 3 and 4 of the canzone, “move cose di lei meco sovente, / che lo ’ntelletto sovre’esse disvia” (awakens often thoughts of her such that my intellect is led astray by them), we may note that the verse is quoted here in a different version: “move sovente cose che fanno disviare l’intelletto” (often stirs thoughts that bewilder the intellect).¹ The lines are not explained, but the meaning is indirectly given by way of an important theme: the superiority of this lady who is above human reason.² We read: … pero che li miei